Triple Band Parasitic Array Antenna for C-X-Ku-Band Application Using Out-of-Phase Coupling Approach - Anubhuti Khare; Rajesh Nema (International Journal of Antennas and Propagation)
Triple band parasitic array antenna for C-X-Ku-band application is presented. The proposed antenna is designed using the concept of parasitic array and out-of-phase coupling approach. The objects of research are to optimize total inductance of geometry by using out-of-phase inductance approach. The out of phase inductance of geometry consists of using two U-patches novel director on the left side of geometry, appropriate dimension of ground plan, and gap coupling between parasitic and active patches. The dimension of the ground plan geometry is 0.5λ mil × 0.5154λ mil. The usable impedance bandwidth of design antenna is “5.8 GHz to 18 GHz” (102% impedance bandwidth) and gain enhancement is up to 11.8 dBi. The proposed antenna can be used for X-Ku band and C-band applications. Both simulated and measured results are presented, which are in good agreement. The proposed antenna was fabricated with a thin copper layer printed on a thin lossy FR4 substrate for low-cost production.